Challenges and Strategies for Training and Development of Health Workforce Improvement in Indonesia - Hutapea, Lyna M. N. (8ISC Abstract Proceedings, 2022)
Nursing is an essential profession in health care services worldwide. The higher the quality of nurses, the better the patient care and other health care services they provide. Although health workforce competence comes in different definitions in different countries, however, in general, it is defined to be a comprehensive statement of proven quality. The aim of this study is to investigate some concerns over the challenges and strategies for health workforce improvement in Indonesia. The method in this study from the literature review to explore those challenges and strategies. The challenges include a shortage and inequitable distribution of medical workers, health workforce policy development and planning are not based on real need, growing and changing demand for health care due to demographic and epidemiological changes will increase the burden on the already ineffective health system. The strategies recommended are better information about the dynamics of the health workforce at the national and subnational levels, modernization of the planning methods for health workforce production and deployment to reflect real demand, to include the private sector in health workers recruitment and deployment, limit the recruitment of publicly funded medical doctors in urban areas, given the fact that more medical doctors settle in urban areas because of private practice opportunities. The public sector should emphasize the placement of medical doctors in rural under-serviced areas to increase the efficient use of public money, modernize health workforce policies based on an evidence-based evaluation of past policies and the quality assurance–certification, strengthen not only the clinical competence of nurses and midwives but also privilege them for providing clinical service in remote areas. Keywords : Health care and services, health workforce improvement.